Microstructure-topology relationship effects on the quasi-static and dynamic behavior of additively manufactured lattice structures. (15th August 2019) - Hazeli, Kavan; Babamiri, Behzad Bahrami; Indeck, Joseph; Minor, Andrew; Askari, Hesam
Abstract: This study demonstrates a relationship between manufacturing variables including design topology and post-processing heat treatment on the porosity distribution, quasi-static, and dynamic behavior of additively manufactured lattice structures (AMLS). Lattice structures were manufactured out of Inconel 718 using selective laser melting technique with four different topologies. The effect of heat treatment on the porosity size and distribution was examined using X-ray computed tomography for as-built (AB), stress relieved (SR), and hot isostatic pressed (HIP) plus solution aged (SA) heat-treatment conditions. It was noticed that reduction of porosity in the as-built samples, as a result of SR, was greater compared the porosity reduction due to the subsequent HIP plus SA. Quasi-static and dynamic loading was conducted and it was found that the deformation trends of each topology were independent of the strain rate. It was also found that the stress relieving heat treatment process enhances the quasi-static and dynamic flow stress after yielding. However, further heat-treating, including HIP and SA, for the same topology were not as effective as the initial SR process. Furthermore, the validity of digital image correlation in measuring average global strain and the validity of using a Kolsky bar for measuring dynamic mechanical behavior of AMLS are discussed. Graphical abstract: Unlabelled Image